Projeto ótimo de um manipulador paralelo planar de dois graus de liberdade - Bolzon, Victor Renan (2018)
This work aims at proposing an alternative procedure for the optimal design of a flexible planar parallel manipulator of two degrees of freedom by using performance indexes based on kinematic and dynamic criteria simultaneously. The complete kinematic and dynamic models allow establishing the workspace size and the elastodynamic performance, respectively. The manipulator design methodology, based on the performance criteria, is obtained by solving a multiobjective optimization problem. The optimal design variables derived from the optimization process are the optimal links lengths. In the optimal design procedure, initially, the performance criteria will be optimized separately. Then, a multiobjective optimization will be performed to obtain the optimal multiobjective design. The Genetic Algorithms were used as a tool to solve the corresponding optimization problems. The results of these optimizations allowed to find the set of optimal solutions denominated the Pareto Front. These results were analyzed in order to determine the structural parameters of the parallel manipulator to find the most suitable configuration for the desired application. Once the optimal and suitable parameters were established, it was carried out the construction of the prototype of the parallel planar manipulator.